2011
DOI: 10.17221/21/2011-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Testing of microbial additives in the rooting of Norway spruce (Picea abies [L.] Karst.) stem cuttings

Abstract: &nbsp;Laboratory-produced alginate-bead inoculum of ectomycorrhizal (ECM) fungi Cortinarius sp. and&nbsp;Gomphidius glutinosus, fungal commercial products ECtovit<sup>&reg; </sup>and Trichomil<sup>&reg;</sup>, bacterial commercial product BactoFil&nbsp;B<sup>&reg;</sup>, and commercial rooting stimulator Vetozen<sup>&reg;</sup> were applied to a peat-perlite (1:2, v:v) rooting substrate of Norway spruce stem cuttings collected from 4-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
3
6
0
Order By: Relevance
“…Nevertheless, a positive effect of Ectovit inoculation on the needle P and K concentrations of Durpeta seedlings was observed. A similar positive influence of Ectovit on needle nutrient concentration of Norway spruce cuttings was described by Repáč et al (2011b). Other chemical characteristics may directly affect the availability of macro-and microelements, as well as the combined effect of physical and chemical properties of substrates (Rincón et al 2007).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Nevertheless, a positive effect of Ectovit inoculation on the needle P and K concentrations of Durpeta seedlings was observed. A similar positive influence of Ectovit on needle nutrient concentration of Norway spruce cuttings was described by Repáč et al (2011b). Other chemical characteristics may directly affect the availability of macro-and microelements, as well as the combined effect of physical and chemical properties of substrates (Rincón et al 2007).…”
Section: Discussionsupporting
confidence: 60%
“…According to Chirino et al (2011), addition of hydrogel to peat-based substrates increased water-holding capacity and positively affected shoot height of containerized Quercus suber seedlings. By contrast, no effect of Ectovit on rooting and biomass production of Norway spruce cuttings was found by Repáč et al (2011b). Moreover, the influence of field inoculation with Ectovit on outplanting performance of Norway spruce seedlings was reported as negligible (Holuša et al 2009, Pešková & Tuma 2010, Repáč et al 2011a.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological conditions of the stock plants (Mitchell et al 2004), time and place of cutting collection (Hannerz et al 1999;Jurásek and Martincová 2004), and environmental conditions (Ragonezi et al 2010;Repáč et al 2011) significantly affect the efficiency of Norway spruce cutting propagation. Initial cutting size is a very important factor involved in rooting ability and growth performance (Burgess et al 1990;Foster et al 2000;Vigl and Rewald 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These data are in agree with that obtained by several authors [3,[12][13][14][15][16], who reported that R. solani and M. phaseolina caused damping-off, root rot and charcoal rot on thyme seedlings. The physiological conditions of the stock plants [39], time and place of cutting collection [40] and environmental conditions [41,42] significantly affect the efficiency of transplanting propagation of many woody and ornamental plants. Koné et al [43] reported that the planting date is an important factor which should be taken into account when developing an integrated strategy to fight infectious diseases.…”
Section: Discussionmentioning
confidence: 99%